Pertumbuhan dan Produksi Jagung Genotip PRG C7, Varietas C7 dan DK 979 dengan Metode Pengendalian Gulma yang Berbeda - Josef Edison Lumbantoruan; Meiriani Meiriani; Lollie Agustina P Putri (Universitas Sumatera Utara, 2015)
The aim of this research was to know the response in growth and yield of maize PRG C7 genotype,C7, and DK 979 variety under different methods of weed control. The research had been conductedat Balai Benih Induk Tanaman Palawija, Sunggal District, North Sumatera on November 2013-Maret 2014 by using a randomized block design non factorial with four treatments (maize PRG C7genotype sprayed with glyphosate, PGR C7 genotype with manual weeding, C7 variety withmanual weeding, and DK 979 variety with manual weeding) and four replications. The resultsshowed that different weed control methods provide no significant effect on the growth of cornPRG C7 genotype, C7 and DK 979 varieties, that production of maize DK 979 variety withmanually weeded significantly larger than C7 maize variety with manually weeded such parametershusks cob weight, unhusks cob weight and number of seeds percob, glyphosate aplication andmanual weeding to maize PRG C7 genotype hadn’t showed the difference to the growth andproduction.Keywords : genotype, variety, glyphosate tolerant, weed control, maize